Surface Flow Analysis as an Efforts Flood Mitigation - Tribhuwana, Awliya; Rohman, Fathur; Farhan, Ohan (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2024)
Problems that often arise in the city of Cirebon are flooding caused by rain, land changes not supported by adequate infrastructure, narrowing of drainage channels and sedimentation of channels. This is the location where flooding often occurs in the Pemuda Street area and its surroundings. Therefore, it is necessary to carry out research on surface flow analysis as an effort to handle floods with the aim of inundation management strategies to reduce excessive rainwater runoff in drainage areas and channels. The research methods used were problem identification, literature study, data collection, analysis and design planning. The results can show that inundation is handled in two ways, first by changing the dimensions of the channel at the initial height H to 0.45m, it still experiences inundation, this is due to the difference in elevation which causes inundation in the channel. There was a change in the flood inundation area to 23,127 ha from the original 58,958 ha, meaning that the flood free area increased from 9,388 ha to 35,831 ha. The second way is by making 378 infiltration wells spread across 34 channels that experience flooding. With these infiltration wells, the flooding can be reduced to a minimum from an area of ​​23,127 ha to 0.040 ha. The success rate for flood management efforts reached 99.908%, with failure being 0.092%. Of the area of ​​68,346 ha, the flood-free area reached 68,306 ha and the remaining inundated area was 0.040 ha..